The Effectiveness of Blended Learning with Discovery Learning Model on Buffer Solution Materials to Improve Science Process Skills - Dicky Saputra; Ila Rosilawati; Gamila Nuri Utami (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
This study aims to describe the effectiveness of discovery learning model on buffer solution materials to improve students’ science process skills. This research is a quasi-experimental study with the matching-only pretest and posttest control group design.Population on this study is all students of class XI IPA of SMAN 1 Sukadana EastLampung in even semester of the 2021/2022 academic year. The sampling techniqueused purposive sampling and obtain class XI IPA 3 and class XI IPA 2 as experimental class and control class, respectively. Hypothesis testing used the analysis of the average post-test value calculation using the difference test of two average by t-test. The results showed that: (1) the average post-test scores of students’ science process skills in the experimental class were significantly different from post-test scores in the control class which is high-categorized of 0,71. Thus, it can be concluded that blended learning with discovery learning model is effective to improve students’ science process skills. Keywords: discovery learning, blended learning, buffer solution, science process skills.